2010
DOI: 10.1177/0893318909358725
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Development as Identity Construction

Abstract: The authors seek to broaden the focus and orientation of social constructionism in leadership development. Previous research has predominantly concerned identity-orientated approaches focused on regulation as opposed to construction of identity. Social constructionism challenges us to view leadership participants as subjects and objects. Using the concept of a “space of action,” the authors focus on places in leadership development where identity work is visible, inducing different kinds of agency. Three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
156
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 36 publications
0
156
0
1
Order By: Relevance
“…This is a more thoroughgoing expectation of obedience than the deference expected by the professional, or the contractual authority of the manager. The development of leaders, and leadership, therefore, requires a more integral focus on the character of leaders -on their intellectual, affective and moral selves as well as on their behavioural competencies (Carroll and Levy 2010;Day and Harrison 2007;Richards 2008), which has been reflected in the content of growing leadership development provision in the public services in the UK, as well as many other countries (Luckcock 2007;Wallace, O'Reilly, Morris and Deem 2011).…”
Section: Ramifications For Practice and Resistancementioning
confidence: 99%
“…This is a more thoroughgoing expectation of obedience than the deference expected by the professional, or the contractual authority of the manager. The development of leaders, and leadership, therefore, requires a more integral focus on the character of leaders -on their intellectual, affective and moral selves as well as on their behavioural competencies (Carroll and Levy 2010;Day and Harrison 2007;Richards 2008), which has been reflected in the content of growing leadership development provision in the public services in the UK, as well as many other countries (Luckcock 2007;Wallace, O'Reilly, Morris and Deem 2011).…”
Section: Ramifications For Practice and Resistancementioning
confidence: 99%
“…The more informed evaluations in the UK healthcare context (13) show that participants report themselves better able to handle the demands of their jobs, but these studies are small-scale -often reporting evaluations of just one programme. More recent critical writings reinforce the importance of engaging research on leadership and management development (6,10,14). Mabey and Finch-Lees (15) identify 5 sets of arguments in relation to the imperative of seeking to identify the value and significance of management and leadership development activities.…”
Section: The Ubiquity and Cost Of Leadership Developmentmentioning
confidence: 99%
“…If we accept that leadership is co-produced by at least leaders, peers and followers (as well as the organisational context in which it occurs), it follows that these parties should be active in participating in leadership learning -going beyond completion as anonymised 'raters' of their managers within the 360 survey instruments and other questionnaires that seek psychometric predictions of leader behaviours. There is considerable risk that the preoccupation with leaders reinforces an exclusive focus on self-awareness, self-development and self-improvement at the expense either of gaining insight into relational dynamics or of an appreciation of the context and environment within with leadership occurs (6,10). This raises a significant question as to how can something that is purportedly relational, and founded on the impact that one person has on many others, merely and purely focus on the one person, the leader?…”
Section: Introductionmentioning
confidence: 99%
“…Critical here is how individuals begin forming a leadership identity. Carroll and Levy (2010) argued how leadership development could be understood differently by participants and, therefore, influence the social construction of participants' leadership identities. Pointedly, the authors identified three responses or means of sensemaking for participants in leadership development programs: "reframing (assimilation), recursivity (complementarity), and polyphronic dialogue (rejection)" (p. 222).…”
Section: Background On Leadership Development Literaturementioning
confidence: 99%